Structural studies of myxoma virus antagonists of innate immunity - O'BYRNE, PETER ERIC (Trinity College Dublin. School of Biochemistry & Immunology. Discipline of Biochemistry, 2019)
Viral evasion of the host immune system is achieved via antagonism of antiviral signalling pathways by the expression of immunomodulating proteins. Vaccinia virus protein C7 and its homologues function as determinants of host range by antagonising the immune response via interaction with its poorly understood target SAMD9. Myxoma virus (MYXV) (the causative agent of myxomatosis), encodes 3 C7 homologues: M062, M063 and M064. M062 alone can complement C7 by binding to SAMD9. Compared to the lab strain Lausanne, MYXV vaccine strain Mav, contains a single residue mutant in M062: I79T, which has been shown to dramatically reduce the binding of M062 to SAMD9 (unpublished data, Dr. Jia Liu). While the crystal structures of C7 and MYXV homologue M064 are known, the structural basis of C7 antagonism remains poorly understood. In this study, the crystal structures of M062-Lau (2.45 Å) and M062-Mav (3.2 Å) are presented. The presence of a novel putative dimerization interface is described, supported by in vitro evidence determined by size-exclusion chromatography multi-angle light scattering. The elongated C terminal tail preserved in clade II C7 homologues is identified in the M062 crystal structures, and shown to mediate interaction between individual M062 proteins. The newly described intermolecular interface comprises a hydrophobic pocket formed by β strands 11 (β11) and 12 (β12), into which Y152 of the C terminal tail is buried, supported by C-H···! bond stabilisation of cis-Pro (P136) by W151. Phylogenetic analysis of the residues proposed to mediate this intermolecular interaction indicates a compensatory adaptation in the OPV C7 homologues (which lack the C terminal tai), introducing an aromatic residue in β12 in order to stabilise the conserved cis-Pro of β12, highlighting the β11,12 interface as a potential region of structural importance in the C7 family. Structural analyses of the pyrin domain of M013 by NMR and circular dichroism are also described, with the presentation of the first viral pyrin domain structural models. The NMR structural models of the M013 pyrin domain identify surface charge residues predicted to influence M013’s antagonism by homotypic Type I interactions with its target: ASC. This study provides a more accurate model with which the molecular basis of M013’s immunomodulation can be predicted.
APPROVED
Keywords: X-ray crystallography; Biochemistry; Virus; Antagonism; Myxoma; Immune